A parasitic coevolution since the Miocene revealed by phase-contrast synchrotron X-ray microtomography and the study of natural history collections - Michel Perreau (Nature Portfolio, 2021)
Abstract The discovery of a new fossil species of the Caribbeo-Mexican genus Proptomaphaginus (Coleoptera, Leiodidae, Cholevinae) from Dominican amber, associated with a new fossil parasitic fungus in the genus Columnomyces (Ascomycota, Laboulbeniales), triggered an investigation of extant species of Proptomaphaginus and revealed the long-enduring parasitic association between these two genera. This effort resulted in the description of the fossil species †Proptomaphaginus alleni sp. nov., and one fossil and two extant species of Columnomyces, selectively associated with species of Proptomaphaginus: †Columnomyces electri sp. nov. associated with the fossil †Proptomaphaginus alleni in Dominican amber, Columnomyces hispaniolensis sp. nov. with the extant Proptomaphaginus hispaniolensis (endemic of Hispaniola), and Columnomyces peckii sp. nov. with the extant Proptomaphaginus puertoricensis (endemic of Puerto Rico). Based on biogeography, our current understanding is that the Caribbean species of Proptomaphaginus and their parasitic species of Columnomyces have coevolved since the Miocene. This is the first occurrence of such a coevolution between a genus of parasitic fungus and a genus of Coleoptera. The phylogenetic relations among Proptomaphaginus species are also addressed based on a parsimony analysis. Fossil specimens were observed by propagation phase-contrast synchrotron X-ray microtomography (PPC-SRμCT) and extant specimens were obtained through the study of preserved dried, pinned insects, attesting for the importance of (i) technological advancement and (ii) natural history collections in the study of microparasitic relationships.